Proses Pembelajaran Marching Band Soul Squad pada Lagu Maju Tak Gentar di Kegiatan Ekstrakulikuler SMP Negeri 3 Palembang: Penelitian - Syahira Lutfiah Azzahrah; Deria Sepdwiko; Rio Eka Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the learning process of Marching Band Soul Squad on the song Maju Tak Gentar in extracurricular activities at SMP Negeri 3 Palembang. The background of this study is the importance of extracurricular activities as a medium for developing students' interests, talents, and character building, especially through musical arts and marching activities such as marching bands. The song Maju Tak Gentar was chosen because it contains patriotic values ​​that are in line with the spirit of nationalism and the goals of character education. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The study was conducted for two weeks involving trainers, marching band participants, and extracurricular instructors. The results of the study showed that the learning process ran systematically through the planning, implementation, and evaluation stages. The trainer used lecture, demonstration, and drill methods to deliver basic wind instrument, percussion, and visual formation techniques. Evaluations were carried out periodically to assess the progress of techniques, discipline, team cohesion, and student character values.